2017
DOI: 10.1097/gox.0000000000001599
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Tensed and Straight Free Jejunum Transfer for the Reduction of Postoperative Dysphagia

Abstract: Background:Free jejunal transfer (FJT) is a standard method of reconstruction after total pharyngo-laryngo-cervical esophagectomy (TPLE) in patients with advanced head and neck cancer. However, it is related to various degrees of postoperative swallowing dysfunction. This study aimed to assess whether the tensed and straight FJT method results in a reduced rate of postoperative dysphagia compared with historical controls.Methods:Patients who were undergoing FJT after TPLE for squamous cell carcinoma of the hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 10 publications
2
6
1
Order By: Relevance
“…Anastomotic stricture was observed in 11% of the patients in this study, which is consistent with the incidence of 3–11% reported previously [4, 6, 7]. Our findings suggest that postoperative radiation therapy may increase the risk of anastomotic stricture, in agreement with the results of a prior investigation [15].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Anastomotic stricture was observed in 11% of the patients in this study, which is consistent with the incidence of 3–11% reported previously [4, 6, 7]. Our findings suggest that postoperative radiation therapy may increase the risk of anastomotic stricture, in agreement with the results of a prior investigation [15].…”
Section: Discussionsupporting
confidence: 93%
“…We observed cervical skin flap necrosis in 34% of patients in our study. The incidence has been reported to range from 1% to 17% [2, 4, 5]. Our study reported a 0% incidence of cases requiring reoperation in operation room, which is similar to the 1% incidence in other study [2].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It is worth noting that some cases in this study were enrolled during the timeframe of our previous report. 3,14 However, the objectives and analysis methods differ entirely.…”
Section: Methodsmentioning
confidence: 99%
“…Free jejunum transfer (FJT) following total pharyngo-laryngo-esophagectomy (TPLE) is globally recognized as a reliable reconstruction method. [1][2][3] However, the intestinal tract is said to be more vulnerable to ischemia than a normal free flap, and basic animal studies have shown that ischemiainduced irreversible tissue degeneration can begin as early as 2 to 3 hours. [4][5][6] In clinical practice, there is a consensus that a shorter ischemic time is better for the FJT, so that the vascular anastomosis is usually completed prior to the completion of the jejunal anastomosis.…”
mentioning
confidence: 99%